Evidence That G(z)-Proteins Couple to Hypothalamic 5-HT(1A) Receptors In Vivo - Serres, F. (J Neurosci, 2000)
Using in situ hybridization and immunoblot analysis, the present studies identified G(z) mRNA and G(z)-protein in the hypothalamic paraventricular nucleus. The role of G(z)-proteins in hypothalamic 5-HT(1A)receptor signaling was examined in vivo. Activation of 5-HT(1A) receptors increases the secretion of oxytocin and ACTH, but not prolactin. Intracerebroventricular infusion (3–4 d) of G(z) antisense oligodeoxynucleotides, with different sequences and different phosphorothioate modification patterns, reduced the levels of G(z)-protein in the hypothalamic paraventricular nucleus, whereas missense oligodeoxynucleotides had no effect. Neither antisense nor missense oligodeoxynucleotide treatment altered basal plasma levels of ACTH, oxytocin, or prolactin, when compared with untreated controls. An antisense-induced decrease in hypothalamic G(z)-protein levels was paralleled by a significant decrease in the oxytocin and ACTH responses to the 5-HT(1A) agonist 8-hydroxy-dipropylamino-tetralin (8-OH-DPAT). In contrast, the prolactin response to 8-OH-DPAT (which cannot be blocked by 5-HT(1A) antagonists) was not inhibited by G(z) antisense oligodeoxynucleotides. G(z)-proteins are the only members of the G(i)/G(o)-protein family that are not inactivated by pertussis toxin. In a control experiment, pertussis toxin treatment (1μg/5 μl, i.c.v.; 48 hr before the 8-OH-DPAT challenge) did not inhibit the ACTH response, potentiated the oxytocin response, and eliminated the prolactin response to 8-OH-DPAT. Thus, pertussis toxin-sensitive G(i)/G(o)-proteins do not mediate the 5-HT(1A) receptor-mediated increase in ACTH and oxytocin secretion. Combined, these studies provide the firstin vivo evidence for a key role of G(z)-proteins in coupling hypothalamic 5-HT(1A)receptors to effector mechanisms.